The Nellie Massacre of 1983 : Agency of Rioters. - Kimura, Makiko (Sage studies on India's north east., 2013)
The Nellie incident, involving the massacre of about 2,000 Muslim villagers, took place during the antiforeigner movement in Assam, in order to drive out illegal Bangladeshi and Nepali immigrants. Unlike the communal "riots" in the other parts of India from the 1980s to 2000s, this was an incident which took place in rural areas. The attackers were part of the Indigenous tribal population, and Assamese Hindus of lower strata. The Nellie Massacre of 1983 is an attempt to search for clues from the narratives of at.